ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KINERJA BIDAN DESA DALAM PELAYANAN ANTENATAL DI WILAYAH KERJA PUSKESMAS PASAR UJUNG BATU KABUPATEN PADANG LAWAS TAHUN 2015 - Siregar, Elvi Diana (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2016)
Antenatal care is health care by professionals to the mother during pregnancy. Village midwife are health workers who are closest to the people, and most are expected to know the state of health of pregnant women, birth mothers and babies in the village. Performance midwife may also be influenced by many factors, including the characteristics of the midwife, internal factors, external and motivation. This research aimed to analyze factors related to the performance of midwives in antenatal care health centers in the region at Pasar Ujung Batu Sub-District, Padang Lawas District. This research was an analytical-survey by using cross sectional study design. The population were all is all midwives in the working area of Pasar Ujung Batu Health Centre, as many as 40 people. All of population were being the sample. Data collected by using questionnaire, and analyzed by multiple logistic regression at 95% Confidence Interval.The research showed that the midwife who had a good performance as much as 37.5 % and the poorer performers were 62.5 %. Statistically, the results also showed that the characteristics (age, marital status), internal factors (income and socio-cultural) , external factors (incentives and coaching) and motivation (sense) is not related to the performance of midwives. While the knowledge, skills, infrastructure and business partners associated with the performance of midwives in the ANC. It is suggested midwives in order to improve its performance by increasing knowledge of the ANC, complementary means of infrastructures that support, establish good cooperation with partners and provide counseling to pregnant women about the importance of ANC to get pregnant women to get the ANC even though the mother is not impaired pregnancy so that mother and fetus remains health.